2023
DOI: 10.1002/art.42477
|View full text |Cite
|
Sign up to set email alerts
|

A 24‐Week, Phase IIa, Randomized, Double‐Blind, Placebo‐Controlled Study of Ziritaxestat in Early Diffuse Cutaneous Systemic Sclerosis

Abstract: Objective We undertook this study to explore the efficacy, safety, and tolerability of ziritaxestat, a selective autotaxin inhibitor, in patients with early diffuse cutaneous systemic sclerosis (dcSSc). Methods NOVESA was a 24‐week, multicenter, phase IIa, double‐blind, placebo‐controlled study. Adults with dcSSc were randomized to oral ziritaxestat 600 mg once daily or matching placebo. The primary efficacy end point was change from baseline in modified Rodnan skin score (MRSS) at week 24. Secondary end point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…12,16 Ziritaxestat is a novel ATX inhibitor 17 that was in development as a treatment for IPF and systemic sclerosis. 18 Phase 2 studies have been completed in patients with IPF 19 and systemic sclerosis 20 ; however, phase 3 trials of ziritaxestat in addition to standard-ofcare treatment in patients with IPF were halted because the benefit-risk profile of ziritaxestat was found to no longer support continuation of these trials. The pharmacokinetics (PK) of ziritaxestat have been reported separately.…”
mentioning
confidence: 99%
“…12,16 Ziritaxestat is a novel ATX inhibitor 17 that was in development as a treatment for IPF and systemic sclerosis. 18 Phase 2 studies have been completed in patients with IPF 19 and systemic sclerosis 20 ; however, phase 3 trials of ziritaxestat in addition to standard-ofcare treatment in patients with IPF were halted because the benefit-risk profile of ziritaxestat was found to no longer support continuation of these trials. The pharmacokinetics (PK) of ziritaxestat have been reported separately.…”
mentioning
confidence: 99%
“…These data suggest that MMF may have some therapeutic effect, but certainly not as robust as anyone would like. When we examine ACR CRISS scores reported in the study by Khanna et al (13), which was a secondary end point, the ziritaxestat and placebo groups both showed high probability of improvement at 24 weeks (0.97 versus 0.83, respectively), again raising the concern for a ceiling effect possibly limiting the ability to discriminate treatments and highlighting the impact of background immune‐suppressing therapy. ACR CRISS was able to discriminate treatment groups in the lenabasum phase II study and tocilizumab and abatacept studies.…”
Section: Study Phase Agent Duration Inclusion Mrss Change In Mrss In ...mentioning
confidence: 99%
“…It is with this backdrop that we read with keen interest the results of the clinical trial of the autotaxin inhibitor, ziritaxestat, conducted by Khanna et al for the treatment of patients with early diffuse cutaneous SSc (13). This study allowed for background immune‐suppressing therapy, which was utilized in the vast majority of patients in both treatment groups of this study.…”
Section: Study Phase Agent Duration Inclusion Mrss Change In Mrss In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ATX-LPA axis may be a potential therapeutic target in IPF, and clinical trials of ziritaxestat, an ATX inhibitor, are being conducted ( 9 , 36 ). The ATX-LPA axis is also involved in skin fibrosis in systemic sclerosis ( 37 ), and a recent clinical trial of ziritaxestat for patients with early diffuse cutaneous systemic sclerosis indicated that inhibition of ATX may improve skin symptoms ( 38 ).…”
Section: Autotaxin and Human Diseasesmentioning
confidence: 99%